Detection of non-polar chemical compositions of in-vitro culture products of pogostemon cablin via gc/ms / Nursuria Md. Setamam and Norrizah Jaafar Sidik - Md. Setamam, Nursuria; Jaafar Sidik, Norrizah (Universiti Teknologi MARA Cawangan Pahang, 2021)
Most of the chemical compound of P. cablin was detected after soil plantation rather than during in-vitro culture since it is expected to have secondary metabolites due to maturity. Theoretically, culture products may not be able to derive many chemical constituents compared to mature plants. However, it is possible to detect the presence of other beneficial compounds from the culture plants. Therefore, the objective of this study is to provide information for these new findings. The experiment was carried out by yielding two types of in-vitro culture products which were callus and microshoot by using plant hormone. After three weeks, high abundances of callus in 0.5 mg/L BAP and 3.0 mg/L NAA were sufficiently acquired by using nodes explant. On the other hand, only a week was required to obtain microshoot from foliar explant by using 0.5 mg/L BAP. Both plant samples were extracted by using hexane solvent for non-polar GC-MS analysis. There are six compounds detected in hexane-callus extraction samples. The highest abundance compound detected is silane (19.04%) and the lowest abundance is tetrasiloxane (8.88%). Only three compounds are found in microshoot which tetrasiloxane is the highest abundance (76.23%) while tetrasiloctane is detected as the lowest (2.37%). Tetrasiloxane which is significantly higher in the microshoot compared to the callus is found to have great beneficial properties such as non-toxic, high compatibility with the lipophilic with extraordinary water repellency and stability that may conclude to play a major role for enhancing plant growth.